Ethanol Production Using SSF Method from Calcium Hydroxide Pretreated Wood Meal - Denny Irawati; Johannes PG Sutapa; Ardi B Firmansyah; Permana A Mardika; Farkhan W Nugroho; Sri N Marsoem (Jurnal Ilmu dan Teknologi Kayu Tropis, 2013)
The objective of this research was to determine the effect of wood waste pretreatment with calcium hydroxide on the yield of ethanol. Wood waste of jati (Tectona grandhis) and sengon (Paraserianthes falcataria) were treated with 20% of CaOH2 solution for 4 days at 50, 60, and 70 °C preceding ethanol production with simultaneous saccharification and fermentation (SSF) method. In the present SSF process, saccharification and fermentation were respectively carried out by the use of cellulase and Saccharomyces cerevisiae in a shaker incubator with 12 rpm at 30 °C for 72 hours. The resulting ethanol was then analyzed using gas chromatography. The chemical compounds of woods (i.e. extractive, holocellulose, alpha-cellulose, pentose and lignin) were also evaluated. It was found that increasing the temperature of alkaline pretreatment increased ethanol yield for both sengon and jati wood wastes. The ethanol yield was in the range of 0.027-0.054%. CaOH2 pretreatment at 70 oC of sengon wood wastes resulted in the highest yield. At elevated temperature, the pretreatment of wood wastes decreased the content of extractive, holocellulose, lignin and pentosan of sengon and jati wood wastes. These were in the contrary to that of increased alpha cellulose content.Key words: calcium hidroxyde, enzymatic saccharification, ethanol, Paraserianthes falcataria, Tectona grandis